Smart and Sustainable Planning for Cities and Regions Results of SSPCR 2019$1 (BOpen Access Contributions /s - Bisello, Adriano; Vettorato, Daniele; Ludlow, David; Baranzelli, Claudia; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2021)
This open access book offers a selection of research papers and case studies presented at the 3rd international conference (3z(BSmart and Sustainable Planning for Cities and Regions(3y(B, held in December 2019 in Bolzano, Italy, and explores the concept of smart and sustainable planning, including top contributions from academics, policy makers, consultants and other professionals. Innovation processes such as co-design and co-creation help establish collaborations that engage with stakeholders in a trustworthy and transparent environment while answering the need for new value propositions. The importance of an integrated, holistic approach is widely recognized to break down silos in local government, in particular, when aimed at achieving a better integration of climate-energy planning. Despite the ongoing urbanization and polarization processes, new synergies between urban and rural areas emerge, linking development opportunities to intrinsic cultural, natural and man-made landscape values. The increasing availability of big, real-time urban data and advanced ICT facilitates frequent assessment and continuous monitoring of performances, while allowing fine-tuning as needed. This is valid not only for individual projects but also on a wider scale. In addition, and circling back to the first point, (big) urban data and ICT can be of enormous help in facilitating engagement and co-creation by raising awareness and by providing insight into the local consequences of specific plans. However, this potential is not yet fully exploited in standard processes and procedures, which can therefore lack the agility and flexibility to keep up with the pulse of the city and dynamics of society. The book provides a multi-disciplinary outlook based on experience to orient the reader in the giant galaxy of smart and sustainable planning, support the transposition of research into practice, scale up visionary approaches and design groundbreaking planning policies and tools.s
Energy System Models for City Climate Mitigation Plans$1 (BChallenges and Recommendations -- Deep Energy Retrofit of Residential Buildings in the Mediterranean Area: the MedZEB Approach -- A Systematic Study of Sustainable Development Goal (SDG) Interactions in the Main Spanish Cities -- City Assessment Tool to Measure the Impact of Public Policies on Smart and Sustainable Cities. The Case Study of the Municipality of Alcobendas (Spain) Compared with Similar European Cities -- Public Research and Development Funding for Photovoltaics in Europe$1 (BPast, Present, and Future -- Urban Density and Household-Electricity Consumption: An Analysis of the Italian Residential Building Stock -- A Possible Circular Approach for Social Perception of Climate Adaptation Action Planning in Metropolitan Cities -- A Spatial Multi-Criteria Decision Support System for Stress Recovery-Oriented Forest Management -- Diagnosis of the State of the Territory in Flanders Reporting about New Maps and Indicators Differentiating between Urban and Rural Areas within Flanders -- Co-creation Pathway for Urban Nature-based Solutions: Testing a Shared-Governance Approach in Three Cities and Nine Action Labs. .s
Keywords: Geography; Environmental sciences -- Social aspects; Regional economics; Spatial economics; Regional Geography; Environmental Social Sciences; Regional and Spatial Economics